Boosting visible-light-driven photocatalytic activity of BiPO4via constructing Schottky junction with Ti3C2 MXene. (July 2020) - Zhang, Like; Yang, Jun; Xie, Taiping; Feng, Shan; Xu, Longjun
Abstract: The low separation efficiency of photoinduced carriers in BiPO4 system limited its photocatalytic application. Here, lotus flower-like heterostructure Ti3 C2 /BiPO4 was constructed via a simple hydrothermal synthesis without surface active agent. The Schottky barrier between BiPiO4 and Ti3 C2 interface could be formed due to the large gap in work function for two components, which efficiently promoted the photoproduced holes extraction, the separation of photogenerated electron-hole pairs and further inhibited photo-corrosion for BiPO4 and strengthened photostability. The heterostructure could totally photodegrade RhB under visible light irradiation for 20 min. The enhanced photocatalytic mechanism was explained in detail in this work. It is hoped that this photocatalytic system will be applied into another wastewater treatment and the used preparation method will be widely applied into many composite materials. Graphical abstract: Unlabelled Image Highlights: Ti3 C2 /BiPO4 Schottky junction was synthesized by a simple method. Ti3 C2 /BiPO4 Schottky junction could promote the interface charge migration. Ti3 C2 /BiPO4 Schottky junction could totally photodegrade RhB dye for 20 min.